2006
DOI: 10.2135/cropsci2006.01.0054
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Distributions in Milling Fractions of Low Phytic Acid Wheat

Abstract: Low phytic acid (LPA) wheat (Triticum aestivum L.) is one approach to improving nutritional quality of wheat by reducing the major storage form of P and increasing the level of inorganic P (P i ), which is more readily absorbed by humans and other monogastric animals. A LPA mutant of wheat, designated Js-12-LPA was isolated following mutagenesis. LPA and wild-type (WT) sib selections of hard red spring wheat families with the pedigree 'Grandin'*4/Js-12-LPA were grown in replicated field trials in 2003 and 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The concentrations of Fe, Mg, and P were all 7-fold higher in the purified globoids as compared with wheat bran. This copurification of Fe and Mg with phytate-P allows us to suggest an association between these compounds and confirms a connection between phytic acid and Mg, verifying what has been documented in low-phytate wheat [Js-12-LPA (11)] and rice [lpa1-1 (24)]. Other minerals such as Ca, Zn, and K increased 5-fold in concentration from wheat bran to purified globoids ( Table 1).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The concentrations of Fe, Mg, and P were all 7-fold higher in the purified globoids as compared with wheat bran. This copurification of Fe and Mg with phytate-P allows us to suggest an association between these compounds and confirms a connection between phytic acid and Mg, verifying what has been documented in low-phytate wheat [Js-12-LPA (11)] and rice [lpa1-1 (24)]. Other minerals such as Ca, Zn, and K increased 5-fold in concentration from wheat bran to purified globoids ( Table 1).…”
Section: Resultssupporting
confidence: 84%
“…In wheat, the greatest concentrations of minerals have been found in the bran (8,9). Direct positive associations between grain phytic acid and Zn have been reported (10), and it has been shown that redistribution within the kernel of phosphate and Mg, from the aleurone layer to the flour, takes place in the wheat mutant Js-12-LPA (11).…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained for maize (Lin et al, 2005), barley (Liu et al, 2007a) and wheat (Guttieri et al, 2006) indicated that lpa mutations do not result in systematic increases or decreases of the mineral contents in these crops.…”
Section: Introductionmentioning
confidence: 91%
“…The high concentration of the phosphorus storage molecule phytate in cereal grains [178] is also problematic, as phytate can also bind Fe and Zn, and decrease absorption of these nutrients in the animal gut. Increasing wheat grain Zn levels by agronomic practices did not result in increased phytate [160], and lines of cereals with mutations that result in low phytate concentration did not consistently have altered levels of Fe or Zn in rice, maize, wheat, barley, or soybean seeds [179][180][181][182][183]. These results suggest that phytate can be decreased in future variety development while Fe and Zn concentrations remain at current levels or higher.…”
Section: Transport Into Seeds and Storage Formsmentioning
confidence: 99%